Benign and Inflammatory Lesions of the Human Female Prostate: A Narrative Review of Diagnostic and Therapeutic Approaches - Garaz, Radion; Stenzl, Arnulf; Tsaur, Igor; Harland, Niklas; Amend, Bastian (Aktuelle Urologie, 2025)
Skene’s glands are recognised as the female equivalent of the male prostate gland. They can be affected by a variety of benign, inflammatory, or malignant conditions.This review critically analyses the current literature on the diagnosis and management of non-malignant lesions associated with Skene’s gland.A comprehensive search of Scopus, Web of Science, and PubMed/MEDLINE was conducted, focusing on non-malignant lesions of Skene’s gland while excluding studies involving newborns and animals.Sixty relevant articles were identified, primarily comprising small case series. The benign lesions reviewed include cysts, hyperplasia, tubular-squamous vaginal polyps, leiomyomas, adenofibromas, and Skene’s gland lithiasis. Inflammatory conditions such as abscesses and female prostatitis were also analysed.Physical examination, ultrasound, cystoscopy, MRI, and micro-ultrasound are essential diagnostic modalities for evaluating Skene’s gland pathologies. Timely conservative or surgical interventions can effectively manage benign conditions, with treatment options typically guided by the severity of symptoms. This review underscores the necessity for further research into the biology of Skene’s gland, particularly regarding potential diagnostic and therapeutic implications, and emphasizes the importance of a routine evaluation of Skene’s gland in urological and gynaecological practice.
Keywords: Skene's gland; periurethral glands; cysts; PSA